332 'Every day was a learning curve': implementing COVID-19 triage protocols in UK ambulance services – a qualitative study. (1st May 2022) - Porter, A; Bell, F; Brady, M; Brown, S; Carson-Stevens, A; Duncan, E; England, L; Evans, B; Foster, T; Gallanders, J; Gunson, I; Harrington, B; et al.
Abstract : Background: TRIM is an evaluation of the triage models used by emergency ambulance services caring for patients with suspected COVID-19 during the pandemic's first wave in 2020. We aimed to understand experiences and concerns of staff about implementation of triage protocols. Method: Research paramedics interviewed stakeholders from four ambulance services (call handlers, clinical advisors, paramedics, managers) and ED clinical staff from receiving hospitals. Interviews (n=23) were conducted remotely using MS Teams, recorded, and transcribed in full. Analysis generated themes from implicit and explicit ideas within participants' accounts (Braun and Clarke 2021), conducted by researchers and PPI partners working together. Results: We identified the following themes: Constantly changing guidelines – at some points, updated several times a day. The ambulance service as part of the wider healthcare system - changes elsewhere in the system left ambulance services as the default. Peaks and troughs of demand - fluctuating greatly over time, and varying across the staff groups. A stretched system - resources were overextended by staff sickness and isolation, longer job times, and increased handover delays at ED. Emotional load of responding to the pandemic - including call centre staff. Doing the best they can in the face of uncertainty - a rapidly evolving situation unlike any which ambulance services had faced before. Conclusion: Implementing triage protocols in response to the COVID-19 pandemic was complex and had to be actively managed by a range of frontline staff, dealing with external pressures and a heavy emotional load. Conflict of interest: None. Funding: UKRI-DHSC Covid-19 Rapid Response Funding.